2015
DOI: 10.1007/s13277-015-3704-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between microRNA-181a and TNFAIP1 regulates pancreatic cancer proliferation and migration

Abstract: We investigated the role of microRNA 181a (miR-181a) and its downstream target tumor necrosis factor, alpha-induced protein 1 (TNFAIP1) in pancreatic cancer regulation. Quantitative real-time PCR (qRT-PCR) was applied to evaluate the gene expression of miR-181a in seven pancreatic cancer cell lines. MiR-181a inhibitor lentivirus (miR-181a-IN) was used to down-regulate miR-181a in Capan-1 and AsPC-1 cells. The effects of miR-181a down-regulation on pancreatic cancer were evaluated by in vitro proliferation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…TNFAIP1 is a tumor suppressor in lung cancer through involving in DNA synthesis and apoptosis [35]. Also, TNFAIP1 was interacted with miR-181a and then involved in proliferation and migration of pancreatic cancer [33]. In this study, when TNFAIP1 was silenced, the migrated and invasive cells were significantly increased compared to that in control group, suggesting the tumor suppressive role of TNFAIP1 in lung cancer.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…TNFAIP1 is a tumor suppressor in lung cancer through involving in DNA synthesis and apoptosis [35]. Also, TNFAIP1 was interacted with miR-181a and then involved in proliferation and migration of pancreatic cancer [33]. In this study, when TNFAIP1 was silenced, the migrated and invasive cells were significantly increased compared to that in control group, suggesting the tumor suppressive role of TNFAIP1 in lung cancer.…”
Section: Discussionmentioning
confidence: 59%
“…Meanwhile, luciferase assay showed that miR-424 negatively regulated TNFAIP1 expression in A549 and H1975 cells. Recently, Zhang and his colleagues demonstrated that miR-181a regulated pancreatic cancer growth and migration through interacting with TNFAIP1 [33], while Zhou et al proved that TNFAIP1 can be directly targeted by miR-372 in gastric carcinogenesis [34]. In addition, it has been said that TNFAIP1 is the target gene for miR-224 in NSCLC invasion and growth [22].…”
Section: Discussionmentioning
confidence: 99%
“…TNFAIP1 is induced by tumor necrosis factor alpha (TNFα) and interleukin-6 (IL6) and has roles in DNA synthesis, DNA repair, and apoptosis (Wolf et al, 1992). TNFAIP1 has tumor suppressive functions in several cancer types, including gastric cancer, NSCLC, pancreatic cancer, and uterine cancer, by supporting tumor growth through NFκB signaling (Cui et al, 2015; Tan et al, 2016; Zhang et al, 2015; Zhou et al, 2013). We propose that reduced NADPH levels upon genetic and pharmacological inhibition of IDH1 cooperates with increased NDUFS1, GNG4 and TNFAIP1 levels to inhibit proliferation and promote ROS-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among the founded potential circRNA/miRNA interactions, hsa_circ_0005785 is potentially able to bind miR181a and miR181b. Moreover, miR-181a played a critical role in regulating pancreatic cancer growth and migration [45]. MiR-181b was associated with the resistance of pancreatic cancer cells to gemcitabine [46].…”
Section: Discussionmentioning
confidence: 99%